ANALISIS TERKAIT RENCANA PENUNDAAN PEMILIHAN UMUM TAHUN 2024 DI INDONESIA - Rasji, Rasji; Clarissa Aurelia Susanto; Liumenti, Liumenti (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The implementation of the people's representation in the administration of the state is a free and honest general election. In Indonesia elections are held every 5 years. Considering that the State of Indonesia adheres to the notion of constitutional democracy. Historically, the Election Law must be formulated and enacted no later than 2023. Issues related to the postponement of the 2024 Election have received much opposition from the public. Bearing in mind that Indonesia is a democratic country and seeing the large number of Indonesian people who reject the idea of postponing the election, the government should consider it to continue with the election. If there is a postponement of the election, then the term of office of the President and Vice President will be extended and that is clearly unconstitutional. Not to mention the term of office of members of the MPR, DPR and DPD and even the DPRD will further add to state and governmental chaos and there could be the possibility of spreading to positions in the structural hierarchy downwards.